Padrões de representação e descrição de recursos informacionais em bibliotecas digitais na perspectiva da ciência da informação: uma abordagem do MarcOnt initiative na era da web semântica - Castro, Fabiano Ferreira de [UNESP] (2008)
The relevancy of not only the Web but also the digital libraries for the diverse branches of Science has stimulated researchers and scientific communities to search for integration solutions, interchange and semantic understanding about the contents that circulate in them. In the present scenary, a strong tendency is verified for the availability of digital contents and the lack of use of adequate patterns for the representation and description of those resources in digital environments, what is pointed by literature as a great concern for the scientific community and focused on this work as a problem of the research. In this context, the proposal of this research is to verify, in the scientific literature, the applicability and functionality of the technologies and instruments available as patterns of representation and description of content and form, in the ambit of digital libraries, with the objective of identifying and characterizing the use and the application of MarcOnt as a tool for the construction of forms of information representation for digital libraries at the present time, highlighting it as an instrument for describing the semantic aspects of the digital contents in these environments. As a methodology, the present work is characterized by being an exploratory and descriptive analysis of the subject, with which it is possible to obtain subsidies for a better and more detailed understanding and comprehension of MarcOnt and the technologies that are included in the ambit of digital libraries for the Semantic Web construction. As a result, it was attempted to demonstrate the application of the MarcOnt tool in a specific informational environment, the JeromeDL Semantic Digital Library, to analyze the fundamentals of Cataloguing the forms of representation of informational resources. That made us define the categories for the future analysis of the system comparing to the MARC21 metadata pattern.